Factors affecting ambulance utilization for asthma attack treatment: understanding where to target interventions. Issue 5 (May 2015) - Raun, L.H.; Ensor, K.B.; Campos, L.A.; Persse, D.
Abstract Objectives Asthma is a serious, sometimes fatal condition, in which attacks vary in severity, potentially requiring emergency medical services (EMS) ambulance treatment. A portion of asthma attacks requiring EMS ambulance treatment may be prevented with improved education and access to care. The aim of this study was to identify areas of the city with high rates of utilization of EMS ambulance for treatment, and the demographics, socio-economic status, and time of day associated with these rates, to better target future interventions to prevent emergencies and reduce cost. Study design A cross-sectional study was conducted on individuals in Houston, TX (USA) requiring ambulance treatment for asthma attacks from 2004 to 2011. Methods 12, 155 EMS ambulance-treated asthma attack cases were linked to census tracts. High rate treatment areas were identified with geospatial mapping. Census tract demographic characteristics of these high rate areas were compared with the remainder of the city using logistic regression. The association between case level demographics and the time of day of asthma attack within the high rate area was also assessed with logistic regression. Results EMS ambulance-treated high rate areas were identified and found to have a utilization incidence rate over six times higher per 100, 000 people than the remainder of the city. There is an increased risk of location in this high rate area with a census tract level increase of percent of population: earning less than $10, 000 yearly income (RR 1.21, 1.16–1.26), which is black (RR 1.08, 1.07–1.10), which is female (RR 1.34, 1.20–1.49) and have obtained less than a high school degree (RR 1.02, 1.01–1.03). Within the high rate area, case level data indicates an increased risk of requiring an ambulance after normal doctor office hours for men compared with women (RR 1.13, 1.03–1.22), for black compared with Hispanic ethnicity (RR 1.31, 1.08–1.59), or for adults (less than 41 and greater than 60) compared with children. Conclusions Interventions to prevent asthma emergencies should be targeted in the high rate area and towards groups identified most at risk. Consideration should be given to improved access to care after normal doctor office hours in these locations. While ambulance treatment reflects the most urgent care needs, these interventions are also expected to reduce the need for emergency room visits.